The cell cycle time in the flat (avillous) mucosa of the human small intestine. Issue 8 (August 1973) - Wright, Nicholas; Watson, Alexander; Morley, Adrian; Appleton, David; Marks, Janet; Douglas, Adrian
Abstract : A hyperproductive mucosal state in gluten-sensitive enteropathy has been proposed on the basis of an elevated mitotic index, but this parameter is dependent on the mitotic duration when used as an index of proliferative status. The mitotic duration was therefore measured in two control patients with normal villous mucosae and in two patients with the flat avillous mucosa of untreated gluten-sensitive enteropathy, using two different stathmokinetic techniques with vincristine. No significant difference in mitotic duration was found but values obtained for cell cycle time showed a halving in the flat mucosae. An increased rate of cell production in the small bowel mucosa of untreated gluten-sensitive enteropathy is thus confirmed.